COUNTRIES DISPOSITION IN THE GLOBAL SCIENTIFIC AND EDUCATIONAL AREA: MANAGEMENT AND CLUSTERING - Марич, Максим; Kholiavko, N; Zhavoronok, A.; Viknianska, A; Kozlovskyi, S. (My University, 2020)
The paper is aimed at developing of suggestions on the directions of internationalization of higher education systems of the world countries on the basis of their clustering by parameters of export and import of educational services. The study involved the use of the cluster analysis method, which was implemented using the software tool for statistical processing of IBM data SPSS Statistics Base (Statistical Package for the Social Sciences). The results of the research showed three important findings. Firstly, globalization leads to a gradual change in the forms and methods of work of higher education Countries Disposition in the Global Scientific and Educational Area: Management and Clustering institutions; it is accompanied by a change in the structure of foreign students. Secondly, in the world market for educational services, India and China hold the lead in terms of imports of educational services; the USA, Great Britain, Australia, Germany, France, China, Russian Federation – by the export of educational services. Thirdly, enhancing competitiveness of universities in the global educational services market requires a transformation of management approaches at both national and institutional levels, namely: towards the development and implementation of holistic strategies for the internationalization of higher education systems and higher education institutions. The authors emphasize the integrative nature of such strategies, which means combining aspects of marketing and branding of universities abroad, modernization of the educational process, internationalization of research, improvement of the infrastructure and organization of leisure for international students.
Keywords: management; higher education system; university; clustering; educational services; internationalization; globalization; strategy